OPTIMIZATION OF ANTIGENICITY ASSAY FOR SYNTHETIC HBSAG EPITOPE CANDIDATE PEPTIDE USING ELISA FOR DEVELOPING MOLECULAR DIAGNOSTIC KIT BASED ON REVERSE VACCINOLOGY - Alifia Alfiantie, Afifah
Viral hepatitis B (HBV) infection is a global health problem that causes fatal diseases in the liver of estimatedly 2 billions people worldwide. In Indonesia itself, one of the efforts to prevent HBV virus infection is by implementing national HBV vaccination program for newborns. However, there are still limitations relating to the development of epidemiological data regarding cases of HBV infection in Indonesia due to the high number of unreported HBV infection as well as the limited facilities available to protect against HBV infection. Therefore, this study aims to prove the antigenicity of synthetic peptide candidates for HBsAg epitope as HBV serology markers that have been predicted previously through reverse vaccinology using the ELISA method as an aid for the development of HBV diagnostics and vaccines. The antigenicity of previously predicted HBsAg epitope peptide is assessed against antibodies present in blood serums of patients with HBV infection by direct, indirect, and competitive ELISA methods. Blood serum used was obtained from HBV positive patients from RSUP Hasan Sadikin, Bandung. Meanwhile, human negative serum from a healthy individual was used for the negative control. Some optimizations were also carried out in this assay, including blocking time, peptide concentration used, and dilution of blood sample. At the blocking stage the incubation time duration of 16 and 24 hours were used, along with variations in the concentration of peptides (1, 10, 20, and 50 ?g/ml) and variation of serum dilution (1:1). The result showed that the synthetic peptide previously predicted to be HBsAg epitope’s antigenicity was successfully proven through indirect ELISA method with the optimal blocking time of 24 hours. The variations in the concentration of peptides used in this study, 1, 10, and 20 ?g ml, were proven to be antigenic to antibodies in HBV patients’ blood serum. These results showed that the peptide can be used in the development of an HBV diagnostic kit based on ELISA though there still are more optimizations and further studies to be done for it to provide an accurate diagnosis. Suggestions for further research include using negative serum from healthy individual that has been negatively tested for anti-HBs antibodies and simultaneously conducting the assay in indirect HBV commercial kit as comparison.